A Norrin/Wnt surrogate antibody stimulates endothelial cell barrier function and rescues retinopathy. Issue 7 (9th June 2021) - Chidiac, Rony; Abedin, Md.; Macleod, Graham; Yang, Andy; Thibeault, Pierre E; Blazer, Levi L; Adams, Jarrett J; Zhang, Lingling; Roehrich, Heidi; Jo, Ha‐Neul; Seshagiri, Somasekar; Sidhu, Sachdev S; et al.
Abstract: The FZD4:LRP5:TSPAN12 receptor complex is activated by the secreted protein Norrin in retinal endothelial cells and leads to βcatenin‐dependent formation of the blood–retina–barrier during development and its homeostasis in adults. Mutations disrupting Norrin signaling have been identified in several congenital diseases leading to hypovascularization of the retina and blindness. Here, we developed F4L5.13, a tetravalent antibody designed to induce FZD4 and LRP5 proximity in such a way as to trigger βcatenin signaling. Treatment of cultured endothelial cells with F4L5.13 rescued permeability induced by VEGF in part by promoting surface expression of junction proteins. Treatment of Tspan12 −/− mice with F4L5.13 restored retinal angiogenesis and barrier function. F4L5.13 treatment also significantly normalized neovascularization in an oxygen‐induced retinopathy model revealing a novel therapeutic strategy for diseases characterized by abnormal angiogenesis and/or barrier dysfunction. SYNOPSIS: This study reports a FZD4:LRP5 antibody agonist (F4L5.13) that activates βcatenin signaling in endothelial cells. F4L5.13 shows efficacy in animal models by normalizing defective retinal angiogenesis and barrier function, providing a novel therapeutic strategy for eye diseases. βcatenin signaling was activated by F4L5.13, which functions as a Norrin surrogate in endothelial cells. Endothelial barrier function was promoted, and VEGF‐induced endothelial permeability was blocked by F4L5.13. Retinal barrier function was restored by F4L5.13 in Tspan12 −/− mice. Pathological neovascularization was reduced by F4L5.13 in an OIR model. Abstract : This study reports a FZD4:LRP5 antibody agonist (F4L5.13) that activates βcatenin signaling in endothelial cells. F4L5.13 shows efficacy in animal models by normalizing defective retinal angiogenesis and barrier function, providing a novel therapeutic strategy for eye diseases.